Novel Phase-Locked Loop Using Adaptive Notch Filter - Xu, Lin; Han, Yang; Zhou, Li-Dan; Yao, Mansoor, Gang; Chen, Chen; Pan, Junmin (Elektronika ir Elektrotechnika, 2009)
A novel three-phase phase-locked loop (PLL) structure suitable for phase and angular frequency tracking from distorted ac utility voltages is presented. The proposed PLL has a simple structure: a conventional three-phase PLL followed by adaptive notch filtering technique and proportional integral controller. The feasibility of the PLL was confirmed by theoretical analysis, and the performance was verified through simulations. The proposed PLL system shows accurate performance under various line voltage disturbances, such as sag, unbalance and harmonics. Ill. 5, bibl. 4 (in English; summaries in English, Russian and Lithuanian).